STRATEGI PERSONAL BRANDING PUSTAKAWAN DI ERA DIGITAL - M. Adrian Nastiar (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
This study aims to determine the personal branding strategy of librarians in the digital era as an effort to improve self-image, professionalism, and the good name of library institutions. In the digital era, librarians are required to be able to build personal branding in the digital era that is credible and inspiring through digital technology and social media. The research method used is a literature study by analyzing the contents of various related literature, which is integrated with Peter Montoya's personal branding theory. The results of the study confirm that personal branding can be done through having distinctive characteristics, positive personalities, having leadership, and utilizing social media as a tool for personal branding. By building a positive and authentic image, a librarian will be able to strengthen their position while improving the role and image of the library, so that they are able to compete and adapt to developments in the times and information technology and social media.